Prevalence and Comparision of Conventional Risk Factors of Cardiovascular Disease Between Clinical and Nonclinical Staff - Khadka, Sunita; Dhungana, Suraksha; Prajapati, Dipanker; Dhungana, Murari; Dangol, Prati Badan; Shakya, Roji; Tamrakar, Binita; Kandel, Unnati; Adhikari, Chandra Mani (Journal of Nepal Health Research Council, 2023)
Background: Cardiovascular disease is the leading cause of death around the globe. A number of studies have shown that hospital staff are vulnerable to cardiovascular disease due to a certain risk of shift duty. It is important to identify cardiovascular risk factors among hospital staff. The aim of this study is, to assess the prevalence of conventional risk factors of cardiovascular disease among hospital staff. Methods: A quantitative cross-sectional study was conducted among staff working at a Shahid Gangalal National Heart Center, a tertiary cardiac center in Nepal. Simple and multiple linear regression analyses were used to examine the association between independent variables and cardiovascular diseases. Statistical analysis was done using SPSS software version 20. Results: A total of 250 hospital staff participated in this study. Among them, 137 were clinical staff and 113 were non-clinical staff. The mean age of clinical staff and the non-clinical staff was 33.69 ± 7.02 years and 38.7 ± 10.58 years respectively with a total of 66.8% females. Prevalence of hypertension, diabetes mellitus, and dyslipidaemia was less in clinical staff compared to non-clinical staff. The mean systolic, diastolic BP was high in non-clinical staff ( P-value 0.001), moreover mean HDL-C was low (1.2 ± 0.2 mmol). BMI was significantly low in clinical staff. [standardized ?= -0.24; 95% CI: -2.90, -0.88]. Conclusions: The prevalence of cardiovascular risk factors were high in non-clinical staff compared to clinical staff. Keywords: Cardiovascular disease; conventional risk factors; hospital staff